Redesign and reconstruction of a steviol-biosynthetic pathway for enhanced production of steviol in Escherichia coli - Moon, Jun Ho; Lee, Kunjoong; Lee, Jun Ho; Lee, Pyung Cheon (Microbial Cell Factories, 2020)
Background: Steviol glycosides such as stevioside have attracted the attention of the food and beverage industry. Recently, efforts were made to produce these natural sweeteners in microorganisms using metabolic engineering. Nonetheless, the steviol titer is relatively low in metabolically engineered microorganisms, and therefore a steviol-biosynthetic pathway in heterologous microorganisms needs to be metabolically optimized. The purpose of this study was to redesign and reconstruct a steviol-biosynthetic pathway via synthetic-biology approaches in order to overproduce steviol in Escherichia coli. Results: A genome-engineered E. coli strain, which coexpressed 5′ untranslated region (UTR)-engineered geranylgeranyl diphosphate synthase, copalyl diphosphate synthase, and kaurene synthase, produced 623.6 ± 3.0 mg/L ent-kaurene in batch fermentation. Overexpression of 5′-UTR-engineered, N-terminally modified kaurene oxidase of Arabidopsis thaliana yielded 41.4 ± 5 mg/L ent-kaurenoic acid. Enhanced ent-kaurenoic acid production (50.7 ± 9.8 mg/L) was achieved by increasing the cellular NADPH/NADP+ ratio. The expression of a fusion protein, UtrCYP714A2-AtCPR2 derived from A. thaliana, where trCYP714A2 was 5′-UTR-engineered and N-terminally modified, gave 38.4 ± 1.7 mg/L steviol in batch fermentation. Conclusions: 5′-UTR engineering, the fusion protein approach, and redox balancing improved the steviol titer in flask fermentation and bioreactor fermentation. The expression engineering of steviol-biosynthetic enzymes and the genome engineering described here can serve as the basis for producing terpenoids - including steviol glycosides and carotenoids - in microorganisms.
Keywords: Alkyl and Aryl Transferases; Arabidopsis; Arabidopsis Proteins; Batch Cell Culture Techniques; Biotechnology; Cytochrome P-450 Enzyme System; Diterpenes, Kaurane; Escherichia coli; Farnesyltranstransferase; Fermentation; Metabolic Engineering; Plant Proteins; Protein Engineering; Recombinant Proteins; Stevia; Kaurene; Kaurenoic acid; Metabolic engineering; Steviol